USE OF MODERN TECHNOLOGIES IN PUBLIC CATERING ESTABLISHMENTS OF UZBEKISTAN - Saidkhonova Umida Ziyodullayevna; Arziyev Dilshod Amriddinovich; Shaumarova Dilnoza Abduhabirovna (Galaxy International Interdisciplinary Research Journal, 2022)
In order to successfully address the problems of innovative development of the restaurant business, it is necessary to monitor the changes in the restaurant business in the national and world markets, with particular emphasis on the main trends in science. and technology.